Changes in the Matrilineal System within Minangkabau Children's Carito - Satya Gayatri; Ida Rochani Adi; Wening Udasmoro (Humaniora, 2019)
This article explores the transformation of the matrilineal system within Minangkabau children’s carito. In general, children’s carito are considered bedtime stories that convey positive values; as such, research into them has focused on values. Children’s carito have been collected through interviews with storytellers who retain the carito within their memories. The memories of these storytellers have changed together with changes in the storytellers themselves and in their environments. To explore the changes in the matrilineal system within the carito, one story has been analyzed over three generations (from grandparents, parents, to children). Changes in the matrilineal system are evidenced through the carito characters’ emergence and disappearance, their actions, and their interactions with their mothers, who—as in the matrilineal system—are central within the carito. Changes, differences, and behaviors within the carito indicate the dynamic transformation of communal families to conjugal families and ultimately nuclear families.